2022
DOI: 10.1161/strokeaha.121.038239
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Ischemic Stroke and Bleeding in Patients With Atrial Fibrillation Who Suffered an Acute Stroke While on Treatment With Nonvitamin K Antagonist Oral Anticoagulants: The RENO-EXTEND Study

Abstract: Background: In patients with atrial fibrillation who suffered an ischemic stroke while on treatment with nonvitamin K antagonist oral anticoagulants, rates and determinants of recurrent ischemic events and major bleedings remain uncertain. Methods: This prospective multicenter observational study aimed to estimate the rates of ischemic and bleeding events and their determinants in the follow-up of consecutive patients with atrial fibrillation who suffer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…Our data also supported that the switch from original DOACs to another DOACs may not lead to a significant benefit in reducing the risk of recurrent IS. [1][2][3][4] However, a benefit may be exhibited if we broaden the outcomes to MACEs since a higher incidence of cardiovascular events may be noted in stroke patients with atrial fibrillation. Further investigation may be warranted to develop an exact algorithm for DOAC failure.…”
Section: Discussionmentioning
confidence: 99%
“…Our data also supported that the switch from original DOACs to another DOACs may not lead to a significant benefit in reducing the risk of recurrent IS. [1][2][3][4] However, a benefit may be exhibited if we broaden the outcomes to MACEs since a higher incidence of cardiovascular events may be noted in stroke patients with atrial fibrillation. Further investigation may be warranted to develop an exact algorithm for DOAC failure.…”
Section: Discussionmentioning
confidence: 99%
“…et al [19] showed that recurrent thromboembolic events in patients with atrial fibrillation who suffered an acute stroke while on treatment with DOACs were associated with hypertension. Carlisle et al [20] also found that hypertension (hazard ratio 1.50; 95% CI 1.09-2.06; P ¼ 0 0.01) was significantly associated with thromboembolic events in a multivariate Cox proportional risk analysis of 18 955 atrial fibrillation patients taking DOACs in the ORBIT-AF I and II registries.…”
Section: Discussionmentioning
confidence: 99%
“…The recently published RENO-EXTEND Study showed a recurrent IS and SE rate of 9.7 per 100 patient-years in patients with NVAF who suffered an acute IS while on treatment with DOACs. 45 Overall, the risk of recurrent IS among patients with NVAF who survived an IS while using warfarin or DOAC can be up to 10× higher when compared with IS risk in DOAC RCTs that enrolled low-risk patient populations. 5,48 IS on OAC, that is, OAC failure, is a particularly difficult problem as there does not seem to be a simple medical management strategy that could reduce the high recurrence risk.…”
Section: Laa Closurementioning
confidence: 99%
“…The recently published RENO-EXTEND Study showed a recurrent IS and SE rate of 9.7 per 100 patient-years in patients with NVAF who suffered an acute IS while on treatment with DOACs. 45…”
Section: Failures In Preventing Af-related Is and Required Researchmentioning
confidence: 99%
See 1 more Smart Citation